Risk factors for congenital heart defects in two populations residing in the same geographic area: a long-term population-based study, Southern Israel. (9th August 2019) - Robinson, Renana; Stavsky, Moshe; Yitshak Sade, Maayan; Krymko, Hanah; Slanovic, Leonel; Novack, Victor; Atar Vardi, Maya; Broides, Arnon; Levitas, Aviva
Abstract: Background: Congenital Heart Defects (CHD) are the most common structural defects of newborns. Southern Israel's population is comprised of Jews (75%) and Arab-Bedouins (25%). The latter has a high rate of consanguinity and low abortion rate compared with the Jewish population, which led us to suspect a higher CHD prevalence in this population. Our aim was to compare maternal risk factors that are associated with CHD in these populations. Methods: All births during 1991–2011 in Soroka University Medical Center (n = 247, 289) with 6078 newborns having CHD were included. To account for same-woman deliveries, general estimating equation models adjusted for ethnicity, gender and birth number were used. Results: The total prevalence of CHD was 24.6/1000 live births, with 21.4 and 30 among Jewish and Bedouin populations, respectively, (p = 0.001). Multi-variant analysis of risk factors for CHD revealed that risk factors common to both populations included conception with fertility medications, sibling CHD, maternal CHD, diabetes mellitus, hypertension and anaemia. Risk factors that were specific for the Bedouin population were – maternal age over 35 years, recurrent pregnancy loss and in vitro fertilisation. However, sibling CHD was more common as a CHD risk factor in the Jewish compared with the Bedouin population (Adjusted OR 10.23 versus 3.19, respectively). Conclusions: The prevalence of CHD is higher in both the Bedouin and Jewish populations than previously reported. Several maternal factors were associated with CHD specifically for a certain population. Risk factors for CHD vary in populations residing in the same geographic area.